Feasibility of Thorium Fuel Cycles in a Very High Temperature Pebble-Bed Hybrid System - L.P. Rodriguez; D. Milian; C.R. García; D.E. Milian; C.A. Brayner; M. Cadavid (PPIKSN-BATAN, 2015)
Nuclear energy presents key challenges to be successful as a sustainable energy source. Currently, the viability of the use thorium-based fuel cycles in an innovative nuclear energy generation system is being investigated in order to solve these key challenges. In this work, the feasibility of three thorium-based fuel cycles (232Th-233U, 232Th-239Pu, and 232Th-U) in a hybrid system formed by a Very High Temperature Pebble-Bed Reactor (VHTR) and two Pebble-Bed Accelerator Driven Systems (ADSs) was evaluated using parameters related to the neutronic behavior such as nuclear fuel breeding, minor actinide stockpile, the energetic contribution of each ﬁssile isotope, and the radiotoxicity of the long lived wastes. These parameters were used to compare the fuel cycles using the well-known MCNPX ver. 2.6e computational code. The results obtained confirm that the 232Th-233U fuel cycle is the best cycle for minimizing the production of plutonium isotopes and minor actinides. Moreover, the inclusion of the second stage in the ADSs demonstrated the possibility of extending the burnup cycle duration and reducing the radiotoxicity of the discharged fuel from the VHTR.Received: 09 February 2015; Revised: 12 May 2015; Accepted: 20 May 2015